Management of Coexistence and Conflicts Between Humans and Macaques in Japan - Léane Depret; Cédric Sueur (Animals)
Conflicts between humans and Japanese macaques (Macaca fuscata) have intensified due to urban and agricultural expansion, reducing natural habitats and pushing macaques into human settlements. This review examines strategies for managing human–macaque coexistence in Japan. Since the 1970s, urbanisation and deforestation have led to increased macaque migration into populated areas, resulting in property damage, crop loss, and, in some cases, aggressive encounters. The growing macaque population underscores the urgency of effective management programmes. Strategies include preventive measures, such as weeding to limit food sources, habitat modification, and community-based interventions to reduce attractants. Non-lethal deterrents, including visual and auditory scare tactics, trained guard animals, and electric fences, have been implemented to discourage macaques from entering human spaces. Physical barriers, such as fences and buffer zones, provide long-term mitigation but require maintenance and community cooperation. Fertility control, including sterilisation and hormonal contraception, offers a long-term population management solution but presents logistical challenges. Lethal control and capture-relocation, though controversial, remain options for particularly problematic individuals. Additionally, integrating One Health and One Conservation approaches into macaque management allows for a holistic strategy that considers disease risks, ecological balance, and ethical implications. A balanced management plan that incorporates multiple strategies, community participation, and continuous monitoring is crucial for mitigating conflicts and fostering sustainable coexistence between humans and macaques.